Tox-positive Corynebacterium ulcerans in hedgehogs, Germany. Issue 1 (1st January 2019) - Berger, Anja; Dangel, Alexandra; Peters, Martin; Mühldorfer, Kristin; Braune, Silke; Eisenberg, Tobias; Szentiks, Claudia A.; Rau, Jörg; Konrad, Regina; Hörmansdorfer, Stefan; Ackermann, Nikolaus; Sing, Andreas
ABSTRACT: Toxigenic Corynebacterium ulcerans may cause both respiratory and cutaneous diphtheria in humans. As a zoonotic emerging pathogen it has been isolated from a wide variety of animals living in captivity, such as livestock, pet, zoo and research animals and additionally in a large number of different wild animals. Here we report the isolation of tox -positive C. ulcerans in four hedgehogs with cutaneous diphtheria and pneumonia, respectively.